2024
DOI: 10.1029/2023jd040284
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of the Volatility Distribution of Organic Aerosols in a Polluted Urban Area: Intercomparison Between Thermodenuder and Molecular Measurements

Wei Chen,
Weiwei Hu,
Zi Tao
et al.

Abstract: To quantify the volatility of organic aerosols (OA), a comprehensive campaign was conducted in the Chinese megacity. Volatility distributions of OA and particle‐phase organic nitrate (pON) were estimated based on five methods: (a) empirical method and (b) kinetic model based on the measurement of a thermodenuder (TD) coupled with an aerosol mass spectrometer; (c) Formula‐based SIMPOL model‐driven method; (d) Element‐based estimations using molecular formula measurements of OA; and (e) gas/particle partitioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 250 publications
(448 reference statements)
1
3
0
Order By: Relevance
“…In contrast, CHO and CHON compounds are mainly IVOC and SVOC, but most of them desorb above 180 °C. The volatility of CHON is consistent with the result of Chen et al that a large fraction of organic nitrate existed either at the higher or lower volatility ranges. It has been reported that the TD-related technique rely on quantitative thermal dissociation of CHON to NO 2 in the gas phase, which occurs at about 350 °C in ∼50 ms at near-ambient pressures, and at 600 °C the dissociation rate coefficient for CHON is about 4 orders of magnitude larger .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, CHO and CHON compounds are mainly IVOC and SVOC, but most of them desorb above 180 °C. The volatility of CHON is consistent with the result of Chen et al that a large fraction of organic nitrate existed either at the higher or lower volatility ranges. It has been reported that the TD-related technique rely on quantitative thermal dissociation of CHON to NO 2 in the gas phase, which occurs at about 350 °C in ∼50 ms at near-ambient pressures, and at 600 °C the dissociation rate coefficient for CHON is about 4 orders of magnitude larger .…”
Section: Resultssupporting
confidence: 90%
“…This method can be divided into two general categories according to whether it is a bulk or speciated organic measurement. The bulk organic measurement systems include an organic carbon/elemental carbon (OC/EC) analyzer and thermodenuder aerosol mass spectrometer (TD-AMS). , The speciated organic measurement systems, mostly employing mass spectrometer, include thermal desorption chemical ionization mass spectrometer (TDCIMS), thermal desorption aerosol GC/MS-FID (TAG), micro-orifice volatilization impactor-chemical ionization mass spectrometer (MOVI-CIMS), thermal-desorption proton-transfer-reaction mass spectrometer (TD-PTR-MS), and filter inlet for gases and aerosols-chemical ionization mass spectrometer (FIGAERO-CIMS). …”
Section: Introductionmentioning
confidence: 99%
“…Future work remains to evaluate the instrument performance in wider ranges of aerosol loadings and source contributions, but the measurements collected here demonstrate that even relatively simple chemical composition measurements can begin to bring insight into the properties, sources, and transformations of ambient aerosols. Validation of some of the measurement parameters, such as volatility and elemental carbon, will require continued in-depth investigation as they are complex parameters that can vary depending on the method by which they are measured. , However, overall the results of this research show great promise for the ChemSpot as a monitoring instrument for unattended measurements of particle mass and composition.…”
Section: Resultsmentioning
confidence: 99%
“…Validation of some of the measurement parameters, such as volatility and elemental carbon, will require continued in-depth investigation as they are complex parameters that can vary depending on the method by which they are measured. 39,40 However, overall the results of this research show great promise for the ChemSpot as a monitoring instrument for unattended measurements of particle mass and composition.…”
Section: Acs Esandt Airmentioning
confidence: 99%